Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1096/fj.202001084r
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effect of phosphodiesterase 4 and 5 inhibitors in deoxycorticosterone acetate‐salt hypertensive uni‐nephrectomized KKA y mice

Abstract: Diabetic nephropathy (DN) is a leading cause of end-stage renal disease (ESRD). Hypertension increases kidney stress, which deteriorates function, and leads to peripheral renal vascular resistance. Long-term hypoperfusion promotes interstitial fibrosis and glomerular sclerosis, resulting in nephrosclerosis. Although hypertension and DN are frequent ESRD complications, relevant animal models remain unavailable. We generated a deoxycorticosterone acetate (DOCA)-salt hypertensive uni-nephrectomized (UNx) KKA y mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…That study also deducted that PGE2 could be used to reduce fibrosis in IPF. Moreover, it was recently shown that PDE4 inhibition significantly decreased CTGF, PAI-1, collagen 1A1 and fibronectin mRNA in TGFβ-stimulated human mesangial cells [47]. These results are in accordance to our results, as the IPF-CM system was previously shown to activate TGF-β signaling [15].…”
Section: Discussionsupporting
confidence: 93%
“…That study also deducted that PGE2 could be used to reduce fibrosis in IPF. Moreover, it was recently shown that PDE4 inhibition significantly decreased CTGF, PAI-1, collagen 1A1 and fibronectin mRNA in TGFβ-stimulated human mesangial cells [47]. These results are in accordance to our results, as the IPF-CM system was previously shown to activate TGF-β signaling [15].…”
Section: Discussionsupporting
confidence: 93%
“…In deoxycorticosterone acetate-induced hyperglycemia, represented by a murine hypertension kidney failure model, mRNA expression was elevated for PDE4A, B and D in the kidney after three weeks [82]. Compound A, a selective PDE4-I (N-[Amino (dimethylamino)methylidene]-4-[(3aS,9bR)-8-ethoxy-7-methoxy-1,3,3a,9b-tetrahydrofuro[3, 4-c]isoquinolin-5-yl]benzamide), significantly suppressed the urinary albumin creatinine ratio, urinary KIM-1 (kidney injury molecule) and MCP-1 (monocyte chemoattractant protein) levels.…”
Section: The Kidneymentioning
confidence: 99%